FACTORS ASSOCIATED WITH BIRTH SPACING AMONG CHILD MARRIAGE COUPLES IN INDONESIA - Puput Kusumawardani Moehas (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Child marriage has been proved resulting adverse outcomes for both groom and brides. Those who married before the age of 15, are more likely to have more than 3 children before they are 24 years old. This, along with the fact that girls are not physically mature enough to give birth, places both mothers and their babies at risk. This study aims to review factors that might influence decision making on spacing birth among child marriage couple in Indonesia. Methods: Data from Riset Kesehatan Dasar (Basic Health Research) of Indonesia 2013 were employed with additional several papers from other countries to strengthen the analysis. The theory of Planned Behavior (TPB) were used to explain that behavior is not fully under control of the individuals. Results: Girls aged of 15-19 were less likely to use contraception. Study shows the birth spacing was affected by attitudes toward behavior. The other factors are subjective norms, where people surrounding are influencing the birth spacing decision. Internal factor such as the affordability of the service may influence them to access the services. External factor such as the availability of the services will help them easier in accessing contraceptive for birth spacing. Conclusions: Child marriage trends are start to decline year by year. Yet, the impact of child marriage needs to be reduced to make a better quality of life of the child marriage. A good practice and positive attitudes to birth spacing will lower the adverse impacts to the brides, and it can give a better outcome for the children as well.